Bridging the gap in outpatient care: Can a daily patient‐reported outcome measure help?. Issue 1 (10th July 2021) - Meryk, Andreas; Kropshofer, Gabriele; Hetzer, Benjamin; Riedl, David; Lehmann, Jens; Rumpold, Gerhard; Haid, Alexandra; Holzner, Bernhard; Crazzolara, Roman
Abstract: Background: Childhood patients have high risks for developing debilitating somatic and mental health side‐effects as a consequence of the many different approaches employed in treating their cancer. Early recognition and close monitoring of clinical and psychological problems are essential in planning appropriate interventions and preventing further deterioration. Case: ePROtect was established as an easy‐to‐use application for daily self‐reporting of symptoms during cancer therapy. ePROtect includes six to eight questions pertaining to seven common symptoms: appetite loss, fatigue, nausea, pain, physical functioning, cognitive impairments and sleep quality. The case of a child diagnosed with Burkitt leukemia developing chemotherapy‐induced oral mucositis in home care is presented to show the therapeutic impact of early symptom detection with a daily web‐based tool. Conclusion: This case highlights how electronic patient‐reported outcome measures (PROM) can directly facilitate patient care in real time and might be incorporated in future clinical routine.